VISCERAL ADIPOSITY INDEX AS HYPERURICEMIA PREDICTOR IN TYPE 2 DIABETES MELLITUS PATIENTS - Cherniaieva, A.A.; Mykytyuk, M.R.; Karachentsev, Iu.I. (World of Medicine and Biology, 2022)
The article examines the relationship between the visceral adiposity index and hyperuricemia in type 2 diabetes mellitus patients. Hyperuricemia was found in 38.1 % of type 2 diabetes mellitus patients. Their visceral adiposity index correlated with decreased tissue sensitivity to insulin-mediated glucose absorption, impaired absorption of postprandial glucose, increased insulin resistance and increased plasma atherogenic potential. Obesity was shown to be an important risk factor for hyperuricemia, and an increased visceral adiposity index is positively associated with its risk in type 2 diabetes mellitus patients. Compared to other indices, visceral adiposity index was more discriminant in determining the hyperuricemia risk than the body mass index, waist circumference, and waist-to-height ratio index.